Evaluasi Kepuasan Pengguna Aplikasi Kai Access Menggunakan Model End User Computing Satisfaction (EUCS) - Aldyan Fanindya Nugraha; Arista Pratama; Asif Faroqi (Pusat Riset dan Inovasi Nasional, 2024)
In the rapidly advancing era of globalization, technology plays a pivotal role in various facets of life, offering manifold benefits. Serving as a vital component in daily tasks and responsibilities, technology has become indispensable. PT. Kereta Api Indonesia has harnessed technological advancements through the KAI Access application, providing customers the convenience of booking train tickets and accessing railway services without the need for physical queues. Despite these advantages, the KAI Access application has garnered low ratings on the Play Store. To enhance user experience and align it with expectations, it is imperative to gauge user satisfaction. This thesis seeks to ascertain the satisfaction level of KAI Access application users by employing Doll & Turkzadeh's End User Computing Satisfaction (EUCS) model, incorporating variables such as Content, Accuracy, Format, Ease of Use, and Timeliness. A sample comprising 400 respondents, specifically those who have previously utilized the KAI Access application, underwent SEM-PLS evaluation utilizing SmartPLS software. The assessment revealed that Content, Format, and Timeliness exert a significant influence on user satisfaction, whereas Accuracy and Ease of Use lack a substantial impact.